Towards a service-based internet 4th European conference, ServiceWave 2011, Poznan, Poland, October 26-28, 2011. Proceedings - Abramowicz, Witold; Llorente, Ignacio M.; Surridge, Mike.; Zisman, Andrea; Vayssière, Julien; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This volume constitutes the refereed proceedings of the Fourth European Conference, ServiceWave 2011, held in Poznan, Poland, in October 2011. The 25 revised full papers presented together with 3 invited presentations were carefully reviewed and selected from numerous submissions. They are organized in topical sections on cloud computing, security, privacy and trust, service engineering fundamentals, business services, and FI-PPP. In addition to the scientific track, 14 extended abstracts of demonstrations covering a wide spectrum of technology and application domains were accepted.
Electronic reproduction.
Keywords: Electronic books; Computer science; Software engineering; Computer software; Information storage and retrieval systems